Titanic disaster! Nickolas Flux and the sinking of the great ship - Yomtov, Nelson; Simmons, Mark (North Mankato, Minnesota Capstone Press, a Capstone imprint, 2015)
When a spontaneous time leap sends Nickolas Flux back to the Titanic's maiden voyage, what's a teenage history buff to do? Try to avoid going down with the ship, of course! From trying to help spot icebergs to getting off the sinking ship safely, Nick must survive one of the most disastrous events of the early 1900s"--
Comic strips
a gift from book africa
1 2 13
Keywords: Titanic (Steamship); Titanic (Steamship) -- Juvenile fiction; Titanic (Steamship) -- Fiction